The Effectiveness of The Development of Digitalization of IPAS Textbooks Based on Higher Order Thinking Skills (HOTS) in The Independent Curriculum - Utami, Arfiati Ulfa; Setyawan, Bagus; Anggraeni, Siti Lutfiah; Afandi, Akhmad; Moniz, Joana Paula Gerabella da Costa (Universitas Negeri Surabaya, 2025)
Objective : This study aims to describe the effectiveness of developing HOTS-based science and natural science textbooks in digital format within the framework of the Independent Curriculum. The Independent Curriculum provides teachers with the flexibility to design a curriculum according to the specific conditions or needs of their schools. Method: This study used the ADDIE model as the instructional design research method. The science and natural science textbooks developed in this study follow the ADDIE model, which includes the analysis stage, design stage, development stage, implementation stage, and evaluation stage. Results: The results of the study include validation and trial outcomes. The validation results of the science and natural science textbooks show an average score of 3.9, categorized as very feasible. Individual and group trials yielded average scores of 85.6 and 87, respectively, indicating the textbooks are very feasible for use based on HOTS criteria. The actual implementation of the textbooks resulted in an average score of 86.1, also classified as very feasible. Novelty: novelty in this study is the development of science and natural science textbooks that are equipped with higher-order thinking (HOTS) questions and presented in digital format. This provides convenience for both teachers and students in accessing as a reference in learning.